Promoting Security Dialogue in the Mediterranean: The Hellenic Presidency and Beyond - Tsinisizelis, Michael J.; Xenakis, Dimitris K.; Chryssochoou, Dimitris N. (Études helléniques / Hellenic Studies, 2003)
Issues of Mediterranean security are examined in the context of broader EU concerns and intentions. The deepening and widening of the European Union is bound to affect its foreign, security and defence policies as well as the normative and institutional orientation of Euromediterranean policy. For the development of the Mediterranean dimension of the European Defence and Security Policy mechanisms are needed to alleviate regional complexity, absorb order-building vibrations and promote a common sense of belonging among the peoples of the region. This article examines the role played by the last EU Hellenic presidency in clarifying and promoting the Mediterranean dimension of EU strategic intentions.